Correction: Decrease in thermal conductivity in polymeric P3HT nanowires by size-reduction induced by crystal orientation: new approaches towards thermal transport engineering of organic materials. Issue 9 (4th March 2015) - Rojo, Miguel Muñoz; Martín, Jaime; Grauby, Stéphane; Borca-Tasciuc, Theodorian; Dilhaire, Stefan; Martin-Gonzalez, Marisol
<x xml:space="preserve">Abstract</x> Correction for 'Decrease in thermal conductivity in polymeric P3HT nanowires by size-reduction induced by crystal orientation: new approaches towards thermal transport engineering of organic materials' by Miguel Muñoz Rojo et al., Nanoscale, 2014, 6, 7858–7865.